Implementasi Kristologi dalam Berapologetika pada Pemimpin GBI ROCK Jabodetabek - Tjahjana, Barah; Edwin, Edwin (STT KINGDOM BALI, 2024)
This study aims to evaluate the understanding of Christology and the need for apologetics among church leaders, specifically within GBI ROCK Jabodetabek Serang. Given the challenges the church faces today, such as attacks from Gnosticism, Docetism, and Arianism, a correct understanding of Christology and apologetic skills are crucial. This research employs a descriptive qualitative method with data collected through semi-structured interviews with 8 church leaders. Data was analyzed using data condensation, data display, and conclusion drawing/verification. The findings indicate: (1) All pastors at GBI ROCK Jabodetabek have a good understanding of Christology except for the concepts of the Trinity and the dual nature of Jesus; (2) They possess an understanding of the qualifications of an apologist, though not fully comprehensive; (3) Most pastors understand the process of implementing apologetics and its application in ministry, but lack a full grasp of concepts, methods, and relevant reference sources. This study highlights the need for enhanced understanding and application of apologetics to address challenges from heretical teachings within the church context